The Relationship of Loneliness with Psychological Well-Being and Rumination in College students: Investigating the Mediating Role of Perceived Stress - Basir Torkashvand; Abdulaziz Aflakseir; Mahdi Imani (روانشناسی بالینی و شخصیت)
Introduction: The present study aimed to investigate the relationship between loneliness, psychological well-being, and rumination among students, as well as to examine the mediating role of perceived stress in this relationship.Method: For this study, 360 students from Shiraz University were selected from eight faculties during the 2021-2022 academic year using a multi-stage cluster sampling method. The methodology of this study is both correlational and descriptive. To gather research data, we utilized several psychological well-being questionnaires: the short form of the Riff (1989) questionnaire, the Rumination Scale by Nolen-Hoeksema and Morrow (1991), the Loneliness Scale by Russell (1996), and the Perceived Stress Scale by Cohen (1983). For data analysis, Pearson correlation tests and regression analysis were conducted, followed by the use of IMOS software for path analysis and model presentation. Results: After examining and meeting the assumptions of path analysis, as well as identifying the proposed model, it was time to test the research model and analyze both the direct and indirect effects. The results of the study indicated that loneliness directly and significantly predicts psychological well-being and rumination. Loneliness significantly predicts psychological well-being and rumination through perceived stress. Finally, the fit indices were analyzed, and these indices demonstrated a favorable fit with the data.Discussion and Conclusion: The findings highlight the importance of loneliness and perceived stress in negative mental health outcomes. Increased levels of loneliness are accompanied by increased levels of perceived stress, which in turn decrease psychological well-being and increase rumination. Therefore, it is crucial to prevent or curtail loneliness and perceived stress among the youth.